2010
DOI: 10.1007/s12291-010-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of low density lipoprotein oxidation by copper

Abstract: Oxidation of Low Density Lipoprotein (LDL) is regarded as a key event in the development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Second, Cu is a powerful catalyst of LDL oxidation in vitro (O'Leary et al, 1992; Patel et al, 1997). When Cu ions are added to LDL, they can react with the lipid hydroperoxides within the LDL to generate peroxyl and alkoxyl radicals that continue LDL oxidation, which is important in the early phases of atherogenesis (Esterbauer et al, 1992, Ghaffari & Ghiasvand, 2010Gieseg et al, 2003;Patel et al, 1997). It is also reported that homocysteine, a risk factor for cardiovascular disease, interacts with Cu to produce oxidant stress (Dong et al, 2013;Kang, 2011;Linder & Hazegh-Azam, 1996).…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…Second, Cu is a powerful catalyst of LDL oxidation in vitro (O'Leary et al, 1992; Patel et al, 1997). When Cu ions are added to LDL, they can react with the lipid hydroperoxides within the LDL to generate peroxyl and alkoxyl radicals that continue LDL oxidation, which is important in the early phases of atherogenesis (Esterbauer et al, 1992, Ghaffari & Ghiasvand, 2010Gieseg et al, 2003;Patel et al, 1997). It is also reported that homocysteine, a risk factor for cardiovascular disease, interacts with Cu to produce oxidant stress (Dong et al, 2013;Kang, 2011;Linder & Hazegh-Azam, 1996).…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…[22] Previous investigation showed that the amount of hydroperoxides accumulated decreased at a CuSO 4 concentration above 20 mmol/L. [23] This may be due to the possible decomposition of unstable hydroperoxides during incubation. To avoid any variation due to decomposition, we chose to use a CuSO 4 concentration equal to 20 mmol/L.…”
Section: Inhibition Effect Of Blueberry Anthocyanins Against Human Ldmentioning
confidence: 98%
“…It is involved in fat metabolism, in particular of lipoproteins: Marginal copper deficiency has been reported as a potential etiologic factor in diseases characterized by disrupted fat metabolism such as nonalcoholic fatty liver disease . The oxidation of low‐density lipoproteins (LDLs) is thought to play a significant role in atherosclerosis: Low copper status is associated with reduced activity of superoxide dismutase (SOD), which favors LDL oxidations.…”
Section: Copper Metabolismmentioning
confidence: 99%